Clonal gametogenesis is triggered by intrinsic stimuli in the hybrid's germ cells but is dependent on sex differentiation† - Tichopád, Tomáš; Franěk, Roman; Doležálková-Kaštánková, Marie; Dedukh, Dmitrij; Marta, Anatolie; Halačka, Karel; Steinbach, Christoph; Janko, Karel; Pšenička, Martin (Biology of reproduction, 2022)
Interspecific hybridization may trigger the transition from sexual reproduction to asexuality, but mechanistic reasons for such a change in a hybrid's reproduction are poorly understood. Gametogenesis of many asexual hybrids involves a stage of premeiotic endoreplication (PMER), when gonial cells duplicate chromosomes and subsequent meiotic divisions involve bivalents between identical copies, leading to production of clonal gametes. Here, we investigated the triggers of PMER and whether its induction is linked to intrinsic stimuli within a hybrid's gonial cells or whether it is regulated by the surrounding gonadal tissue. We investigated gametogenesis in the Cobitis taenia hybrid complex, which involves sexually reproducing species (Cobitis elongatoides and C. taenia) as well as their hybrids, where females reproduce clonally via PMER while males are sterile. We transplanted spermatogonial stem cells (SSCs) from C. elongatoides and triploid hybrid males into embryos of sexual species and of asexual hybrid females, respectively, and observed their development in an allospecific gonadal environment. Sexual SSCs underwent regular meiosis and produced normally reduced gametes when transplanted into clonal females. On the other hand, the hybrid's SSCs lead to sterility when transplanted into sexual males but maintained their ability to undergo asexual development (PMER) and production of clonal eggs, when transplanted into sexual females. This suggests that asexual gametogenesis is under complex control when somatic gonadal tissue indirectly affects the execution of asexual development by determining the sexual differentiation of stem cells and once such cells develop to female phenotypes, hybrid germ cells trigger the PMER from their intrinsic signals.
Keywords: gonial stem cell transplantation; Animals; Female; Germ Cells; Gametogenesis; ženské pohlaví; Sex Differentiation; premeiotic endoreplication; diploidie; máloostní; zárodečné buňky; hybridization; Male; gametogeneze; Diploidy; Cypriniformes; zvířata; mužské pohlaví; sexuální diferenciace; asexuality